Implementation of Official’s Mutation in Bengkulu’s Government: Fiqh Siyasah Perspective - Miinudin Miinudin; Mia Audyna (Institut Agama Islam Negeri (IAIN) Curup, 2022)
Implementation of the mutation of officials was carried out by the Mayor of Bengkulu, which based on a case study that occurred in 2018, the mutation was considered to violate the law and was also considered to be legally flawed and not in accordance with existing regulations. The purposes of this study include: (1) To explain the implementation of mutations in the government of Bengkulu City. (2) To analyze the views of fiqh siyasa on the implementation of the Bengkulu City transfer. The method used in writing this journal is field researchusing qualitative methods. The technique used in collecting data is by observing, interviewing, and documenting. The data analysis used in this study is qualitative analysis using deductive reasoning methods, namely describing general matters and then drawing specific conclusions according to the problems discussed in this study. The results of this study found that in practice, the transfer of officials in the Bengkulu City government had not been carried out properly, as evidenced by case studies of violations that occurred in 2018 and 2019 where the replacement of officials was carried out without written approval from the Minister of Home Affairs. Meanwhile, in the fiqh analysis, siyasah is known as the wizarah namely as a person who is an assistant to the head of state with authority or power in the field of government. And in practice it is still contrary to the principle of wizarah where every assistant to the caliph must pay attention to the rules and regulations that have been set.